2006
DOI: 10.1038/sj.onc.1209374
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyltransferase 2 genetic polymorphism: effects of carcinogen and haplotype on urinary bladder cancer risk

Abstract: A role for the N-acetyltransferase 2 (NAT2) genetic polymorphism in cancer risk has been the subject of numerous studies. Although comprehensive reviews of the NAT2 acetylation polymorphism have been published elsewhere, the objective of this paper is to briefly highlight some important features of the NAT2 acetylation polymorphism that are not universally accepted to better understand the role of NAT2 polymorphism in carcinogenic risk assessment. NAT2 slow acetylator phenotype(s) infer a consistent and robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
134
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 117 publications
(122 reference statements)
5
134
2
2
Order By: Relevance
“…28 It has been shown that rate of N-acetylation to detoxify the aromatic amines is less in slow acetylators so these carcinogens are accumulated in the affected tissue. 8 The codon 751 polymorphism, which may change the activity of the enzyme, is located in COOH terminal domain of XPD. This region of the protein possesses helicase activity and deletion in this region causes reduced XPD DNA helicase activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…28 It has been shown that rate of N-acetylation to detoxify the aromatic amines is less in slow acetylators so these carcinogens are accumulated in the affected tissue. 8 The codon 751 polymorphism, which may change the activity of the enzyme, is located in COOH terminal domain of XPD. This region of the protein possesses helicase activity and deletion in this region causes reduced XPD DNA helicase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Since polymorphisms at 481 and 803 np do not change the acetylation status so variant alleles/haplotypes, having at least one variant nucleotide at one of the remaining 3 polymorphic sites (341, 590 and 857 np), are known as slow acetylating alleles (e.g., NAT2*5B, NAT2*6B, NAT2*7A, etc). 8 So, individuals carrying 2 rapid acetylating alleles (such as NAT2*4/NAT2*4 genotype) in the pair of chromosomes are rapid acetylators; carrying 2 slow acetylating alleles (such as NAT2*5A/ NAT2*5B genotype) are slow acetylators; and carrying one slow and one rapid acetylating allele (i.e., NAT2*4/NAT2*5A genotype) is intermediate acetylators.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…NAT2 acetylation phenotype was assigned at the University of Louisville (by DWH) based on in vivo and in vitro data on allelic variation in catalytic activity [13]. For analysis of NAT2 phenotypes, individuals homozygous for NAT2 rapid-and slow-acetylator alleles were designated as rapid-and slow-acetylators, respectively; individuals possessing one rapid-and one slow-acetylator allele (heterozygotes) were designated as intermediate-acetylators [26].…”
Section: Discussionmentioning
confidence: 99%